2018
DOI: 10.3390/joitmc4030022
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency Analysis of the Royalty System from the Perspective of Open Innovation

Abstract: Abstract:The purpose of this study is to suggest efficiency improvement using the analysis of the efficiency of the royalty system for government-funded research institutes (GRIs) belonging to the National Research Council of Science & Technology (NST). Twenty three GRIs' royalty incomes and expenses (2013)(2014)(2015) were analyzed using the data envelopment analysis (DEA) model. First, Research Model 1 was used to find out if the obligated expense category's distribution ratio were efficient. Five Charnes, C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Paper Twenty-one studies technology in innovation systems from an ecosystem innovation perspective, with relation to technology convergence [100]. Paper Twenty-two is about fuzzy analytic hierarchy process (AHP), data envelopment analysis (DEA), and managerial analysis for supplier selection and development from an open innovation perspective [101]. Paper Twenty-three is about promoting the development of enterprise niches through a case study on China's organizational ambidexterity from the perspective of a platform business eco-model evolution [102].…”
Section: Editorialmentioning
confidence: 99%
“…Paper Twenty-one studies technology in innovation systems from an ecosystem innovation perspective, with relation to technology convergence [100]. Paper Twenty-two is about fuzzy analytic hierarchy process (AHP), data envelopment analysis (DEA), and managerial analysis for supplier selection and development from an open innovation perspective [101]. Paper Twenty-three is about promoting the development of enterprise niches through a case study on China's organizational ambidexterity from the perspective of a platform business eco-model evolution [102].…”
Section: Editorialmentioning
confidence: 99%
“…Aristovnik [70] deduced the significance of ICT effects by measuring the effects of ICT on education performance in EU and OECD countries. Hawng et al [71] measured the efficiency of the Royalty System to assert the R&D environment, a new approach from the perspective of open innovation. It deduced the potential improvement level of inefficient organizations and proposed direction.…”
Section: Data Envelopement Analysismentioning
confidence: 99%
“…The data envelopment analysis (DEA) model was used to analyze the efficiency of R&D agencies. DEA is an analysis technique mainly used to measure the efficiency of research subjects in various fields [15]. The DEA model, first proposed by Charnes, Cooper and Rhodes (1978) [16], is based on the concept of Farrell (1957) [17] of relative efficiency.…”
Section: Data Envelopment Analysismentioning
confidence: 99%
“…Park et al (2011) [27] assessed the efficiency of R&D projects supported by the government in scientific and technological areas such as papers and patents by utilizing science and technology investment and performance data of NTIS (National Science and Technology Information Service). Hwang et al (2019) [15] suggested improving the efficiency of public R&D through the improvement of the royalty system. Hwang et al (2019) [6] suggested improving the pro-ductivity of public R&D by improving the operational-efficiency of public R&D agencies.…”
Section: The Role Of Public Randd Agencies As the Engine Of Open Innovation Found From Dea Analysismentioning
confidence: 99%